Integration of Da'wah Ethics and Psychology in Banjar Culture: A Humanistic Approach to Religious Communication - Ariani, Anita; Fuadi, Anwar; Idris, M.; Ermalianti, Ermalianti (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Religious communication in multicultural societies requires approaches that are both ethically sound and culturally sensitive. While da'wah efforts in Indonesia often emphasize textual or dogmatic methods, they frequently overlook the psychological dimensions of communication and the importance of local wisdom. This study addresses that gap by exploring how da'wah ethics and psychological principles can be integrated within the cultural framework of the Banjar community in South Kalimantan. Known for their strong Islamic values and traditions such as ba’iman (faith), ba’adab (civility), and ba’budaya (cultural identity), the Banjar people provide a relevant context for examining localized religious outreach. Employing a qualitative-descriptive approach with literature analysis, the study uses a humanistic communication framework that prioritizes empathy, respect, and psychological awareness in message delivery. The findings show that aligning da'wah with Banjar cultural values and emotional norms not only enhances message receptivity but also reduces resistance to religious messages. This integrated approach fosters deeper engagement, strengthens social cohesion, and makes religious communication more relevant to the lived experiences of the audience. The study contributes to the discourse on contextualized da'wah by proposing a model that respects both Islamic ethical principles and the cultural psychology of local communities.